A novel gene-pair signature for relapse-free survival prediction in colon cancer - Chen P (Cancer Management and Research, 2018)
Peng-fei Chen,1–3,* Fan Wang,1,2,* Zi-xiong Zhang,4,* Jia-yan Nie,1,2 Lan Liu,1,2 Jue-rong Feng,1,2 Rui Zhou,1,2 Hong-ling Wang,1,2 Jing Liu,1,2 Qiu Zhao1,2 1Department of Gastroenterology, Zhongnan Hospital of Wuhan University, Wuhan 430071, China; 2Hubei Clinical Center & Key Lab of Intestinal & Colorectal Diseases, Wuhan 430071, China; 3Department of Gastroenterology, The Central Hospital of Enshi Autonomous Prefecture, Enshi 445000, China; 4Department of Otolaryngology, The Central Hospital of Enshi Autonomous Prefecture, Enshi 445000, China *These authors contributed equally to this work Background: Colon cancer (CC) patients with early relapse usually have a poor prognosis. In this study, we aimed to identify a novel signature to improve the prediction of relapse-free survival (RFS) in CC. Methods: Four microarray datasets were merged into a training set (n=1,045), and one RNA-sequencing dataset was used as a validation set (n=384). In the training set, microarray meta-analysis screened out 596 common RFS-related genes across datasets, which were used to construct 177,310 gene pairs. Then, the LASSO penalized generalized linear model identified 16 RFS-related gene pairs, and a risk score was calculated for each sample according to the model coefficients. Results: The risk score demonstrated a good ability in predicting RFS (area under the curve [AUC] at 5 years: 0.724; concordance index [C-index]: 0.642, 95% CI: 0.615–0.669). High-risk patients showed a poorer prognosis than low-risk patients (HR: 3.519, 95% CI: 2.870–4.314). Subgroup analysis reached consistent results when considering multiple confounders. In the validation set, the risk score had a similar performance (AUC at 5 years: 0.697; C-index: 0.696, 95% CI: 0.627–0.766; HR: 2.926, 95% CI: 1.892–4.527). When compared with a 13-gene signature, a 15-gene signature, and TNM stage, the score showed a better performance (P<0.0001; P=0.0004; P=0.0125), especially for the patients with a longer follow-up (R2=0.988, P<0.0001). When the follow-up was >5 years (n=314), the score demonstrated an excellent performance (C-index: 0.869, 95% CI: 0.816–0.922; HR: 13.55, 95% CI: 7.409–24.78). Conclusion: Our study identified a novel gene-pair signature for prediction of RFS in CC. Keywords: colon cancer, relapse-free survival, gene pair, prognosis